A case of idiopathic portal hypertension with large intrahepatic portal-hepatic venous shunt - TSUJIMOTO, Tatsuhiro; NAKAJIMA, Yoshiyuki; FUKUI, Kenichi; KOJIMA, Hideyuki; YOSHIJI, Hitoshi; KIKUKAWA, Masaji; FUKUI, Hiroshi; TSUJII, Tadasu; KOIZUMI, Masaki; NAKANO, Hiroshige; MATSUMURA, Masahiko (Kanzo, 1996)
We report a case of idiopatic portal hypertension with large intrahepatic portal-hepatic venous shunt. A 56-year-old female was admitted to our hospital because of general fatigue and flapping tremor. Ultrasonography and Computed tomography (CT) showed large intrahepatic potal-hepatic venous shunt. Portgram showed anastomosis between the branches of hepatic vein and typical "Shidare-yanagi" sign was noted. In wedge biopsy of the liver, narrowing of the portal vein, orbicular fibrosis around the portal vein and abnormal vessels were seen. The angiography and histopathological findings were consistant with idiopathic portal hypertension. It was supposed that the intrahepatic portal-hepatic venous shunt became large as the progression of portal hypertension.